Dominican Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper provides a brief overview of the Dominican Republic authorities' structural reform efforts in the 1990s. The paper provides a history of trade reforms, which form an integral part of the structural reform agenda. It presents a review of fiscal policy during the 1990s. The paper discusses the major tax reforms and improvements in administration that were implemented during the 1990s, as well as developments in expenditure policy. A survey of fiscal policy proposals considered by the authorities, aimed at reinforcing the gains already achieved is also presented.